Characterization of the Copy Number and Variants of Deformed Wing Virus (DWV) in the Pairs of Honey Bee Pupa and Infesting Varroa destructor or Tropilaelaps mercedesae - Wu, Yunfei; Dong, Xiaofeng; Kadowaki, Tatsuhiko (Frontiers in Microbiology, 2017)
Recent honey bee colony losses, particularly during the winter, have been shown to be associated with the presence of both ectoparasitic mites and Deformed Wing Virus (DWV). Whilst the role of Varroa destructor mites as a viral vector is well established, the role of Tropilaelaps mercedesae mites in viral transmission has not been fully investigated. In this study, we tested the effects that V. destructor and T. mercedesae infestation have on fluctuation of the DWV copy number and alteration of the virus variants in honey bees by characterizing individual pupae and their infesting mites. We observed that both mite species were associated with increased viral copy number in honey bee pupae. We found a positive correlation between DWV copy number in pupae and copy number in infesting mites, and the same DWV type A variant was present in either low or high copy number in both honey bee pupae and infesting V. destructor. These data also suggest that variant diversity is similar between honey bee pupae and the mites that infest them. These results support a previously proposed hypothesis that DWV suppresses the honey bee immune system when virus copy number reaches a specific threshold, promoting greater replication.